Governing land: reflections from IFPRI research - Dohrn, Stephan (International Food Policy Research Institute, 2006)
Land is still among the most important assets of the rural population in the developing world. Land resources are governed by a variety of tenure systems based on statutory, customary, or religious law. At the same time, many national, subnational, and local institutions administer the application and enforcement of these laws, relying on a wide variety of policies, rules, and regulations that promote different practices for using and managing land and land-based resources. IFPRI contributes to land policy debates by demonstrating the importance of land policy and its impact on rural people. This occurs across multiple dimensions, including people’s livelihoods, the sustainability of the resource base, and the effectiveness of the institutions that govern land. This brief summarizes findings of relevant IFPRI research on land management and governance to promote strategies and policies targeted toward the achievement of gender equity, poverty reduction, and sustainable resource management.